Gender Violence, the Law, and Society 2022
DOI: 10.1108/978-1-80117-127-420221005
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation Microaggressions in South Africa

Abstract: Discrimination against LGBTQ1 people in South Africa has shifted from overt hate crimes to covert microaggressions. Microaggression is a term used in psychology to describe casual discrimination against socially marginalised groups, and they occur in three forms: microassaults, microinsults and microinvalidations. Microassaults include verbal and non-verbal discriminatory behaviours. Microinsults include actions or statements which demean a person's identity, and microinvalidations negate the thoughts, feeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Nair’s (2020) qualitative research with five LGBT+ South Africans of Indian descent also found that participants struggled to deal with heteronormative family expectations and community expectations, despite diverse coming out experiences. Dayal’s (2020) qualitative research with four gay men found similar themes of frustration about hetero-cis-normative gender expectations and heterosexist language use, negative coming out experiences, fears of shaming one’s family or community, reconciling religion and sexual orientation, and the pressure to lead a double life.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Nair’s (2020) qualitative research with five LGBT+ South Africans of Indian descent also found that participants struggled to deal with heteronormative family expectations and community expectations, despite diverse coming out experiences. Dayal’s (2020) qualitative research with four gay men found similar themes of frustration about hetero-cis-normative gender expectations and heterosexist language use, negative coming out experiences, fears of shaming one’s family or community, reconciling religion and sexual orientation, and the pressure to lead a double life.…”
Section: Discussionmentioning
confidence: 88%
“…The related Practice Guidelines for Psychology Professionals Working with Sexually and Gender Diverse People (McLachlan et al, 2019) also recommend more nuanced, intersectional understandings of the lives of LGBT+ people in South Africa. There is a growing recognition within South African psychology about the multiple forms of discrimination against queer people, and the intersecting variables of minority stress that impact upon LGBT+ identity, health, and well-being (Dayal, 2020; Shefer, 2019; Zway & Boonzaier, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation